2013
DOI: 10.2118/163069-pa
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Heat-Transfer Mechanism in the Steam-Assisted Gravity-Drainage (SAGD) Process and Comparing the Conduction and Convection Flux in Bitumen Reservoirs

Abstract: Even at constant inlet and outlet boundary conditions (represented by gas and liquid mass flow rates and separator pressure, respectively), unsteady-state flow may occur in a pipeline/riser system operating at relatively low gas and liquid flow rates. The cyclic unsteady-state flow characterized by large-amplitude pressure and flow rate fluctuations has been referred to as severe slugging. This study is an experimental investigation of flow instabilities, especially severe slugging, in a relatively long hilly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Heat convection also affects chamber growth by observed rising fingers. A series of new analytical models accounting for both heat conduction and convection have been developed. These studies indicated that effects of convection were functions of temperature and water saturation. A higher saturation and a lower temperature in reservoirs usually resulted in an augmented heat convention.…”
Section: Steam-assisted Gravity Drainage (Sagd)mentioning
confidence: 99%
“…Heat convection also affects chamber growth by observed rising fingers. A series of new analytical models accounting for both heat conduction and convection have been developed. These studies indicated that effects of convection were functions of temperature and water saturation. A higher saturation and a lower temperature in reservoirs usually resulted in an augmented heat convention.…”
Section: Steam-assisted Gravity Drainage (Sagd)mentioning
confidence: 99%
“…Although it is an assumption, the resultant equation provides an understanding of the role of convection. In 2013, Irani and Ghannadi [5] conducted a certain degree of research on the convection caused by the water phase, and they established a steam-assisted gravity drainage heat transfer model that considered thermal convection. Irani believed in the heat transfer method of thermal convection, but their research on thermal convection was only carried out under ideal conditions, while actual reservoir conditions are far from ideal and can, of course, deviate considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Although most researchers supported conductive heat transfer, researchers still hold the point that heat convection is more significant under some circumstances. ,, Furthermore, the precise proportion of conduction and convection in total heat transfer is still inconclusive. Previous researchers adopted a variety of research methods, such as theoretical analysis, experiment, or numerical simulation, and obtained different ratios of convective heat flux to conductive heat flux (<5, >50, <10, or <1%).…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of bitumen drops sharply in the immediate vicinity of the steam chamber interface, where bitumen is mobile at high temperatures. However, the heated bitumen does not flow into the farther cold reservoir in the direction normal to the boundary of the steam chamber because of its extremely low mobility that is caused by a low relative permeability, but rather flows essentially along the steam chamber interface downward to the oil accumulation area above the production well. , Therefore, water flow is considered as the single phase that transfers thermal energy to the cold reservoir in the heat convection process . In previous studies, heat convection is mainly considered to be caused by the condensate flow under pressure difference between the steam chamber and the original reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation